POCUS in a Patient with Acute Heart Failure, Diagnosis of an Unusual Etiology: A Case Report - Narvaez-Orozco, Alejandro; Agudelo-Quintero, Cristian Camilo; Arcila-Cano, Nicolás; Atencia-Flórez, Carlos José (Iatreia)
Introduction: Heart failure represents a global public health concern. The majority of patients presenting to emergency departments have a known diagnosis and manifest an acutely decompensated chronic heart failure, while a smaller proportion present as de novo cases. Beyond identifying clinical manifestations, the diagnostic process should focus on identifying potential etiologies, which may initially be suspected through patient history and physical examination. Objectives: To describe, explore, and evaluate the utility of Point-of-Care Ultrasound (POCUS) in the initial assessment of heart failure syndrome in an emergency department setting. Methods: We present a case of a 60-year-old female patient with no significant medical history who presented to the emergency department with clinical symptoms of heart failure. Auscultation findings and ultrasound examination performed with a pocket device facilitated decision-making and ultimate treatment of an unusual etiology. Conclusions: Point-of-Care Focused Cardiac Ultrasound (FOCUS) may provide added value in the initial approach to heart failure syndrome.